2010
DOI: 10.1002/cphc.201000200
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen Reduction by Cobalt(II) Octaethylporphyrin at Liquid|Liquid Interfaces

Abstract: Oxygen reduction catalyzed by cobalt(II) (2,3,7,8,12,13,17,18‐octaethylporphyrin) [Co(OEP)] at soft interfaces is studied by voltammetry and biphasic reactions. When Co(OEP) is present in a solution of 1,2‐dichloroethane in contact with an aqueous acidic solution, oxygen is reduced if the interface is positively polarized (water phase versus organic phase). This reduction reaction is facilitated when an additional electron donor, here ferrocene, is present in excess in the organic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…In the case of the ORR, oxygen is also required and can partitionb etween both liquid phases under ambient conditions, with the source dependentu pon the reactionm echanism. Part of the interest in using ITIES systems for these reactions stems from the inherent advantages comparedt osingle-liquid-phases ystems, including the ability to isolate reactants until as ufficient Galvanip otential (D0)i sa pplied, availability of lipophilic reducing agents and partitioning of reaction products out of the organic phase and away from the reducing agent: [7,41] Ar ange of catalysts have been used to increase the rate of both reactions at the ITIES, including Pt, Pd [29] and Cu [38] nanoparticles (NPs) as well as various transition-metal carbides, borides and dichaldogenides [30,33] for the HER and porphyrins (with Co [6,8,9,13,14,16,21] or metal free [10,11,22,24] ), aniline derivatives, [12,17] phthalocyanines [20,25] as well as Pt [5] and Au [23] NPs for the ORR. These catalysts are generally either present in the organic phase or adsorbed at the ITIES.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the ORR, oxygen is also required and can partitionb etween both liquid phases under ambient conditions, with the source dependentu pon the reactionm echanism. Part of the interest in using ITIES systems for these reactions stems from the inherent advantages comparedt osingle-liquid-phases ystems, including the ability to isolate reactants until as ufficient Galvanip otential (D0)i sa pplied, availability of lipophilic reducing agents and partitioning of reaction products out of the organic phase and away from the reducing agent: [7,41] Ar ange of catalysts have been used to increase the rate of both reactions at the ITIES, including Pt, Pd [29] and Cu [38] nanoparticles (NPs) as well as various transition-metal carbides, borides and dichaldogenides [30,33] for the HER and porphyrins (with Co [6,8,9,13,14,16,21] or metal free [10,11,22,24] ), aniline derivatives, [12,17] phthalocyanines [20,25] as well as Pt [5] and Au [23] NPs for the ORR. These catalysts are generally either present in the organic phase or adsorbed at the ITIES.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has also investigated the ORR at the w/DCE interface quite extensively since 2008 [16], including the ORR at the ITIES by direct lipophilic electron donors such as different ferrocene derivatives [16][17][18] or tetrathiafulvalene [19]. We also found that the reaction can be catalyzed by different porphyrins [20][21][22][23][24][25][26][27] and dodecylaniline [28], and a novel fuel cell concept based on molecular catalysis of oxygen reduction at a liquid/liquid interface was introduced [29]. More recently, the mechanism of ORR catalyzed by the biomimetic cofacial bis-metalloporphyrins at the liquid/liquid interface was also studied, with the help of density functional theory (DFT) [30].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have also investigated the oxygen reduction at the ITIES by direct electron donors such as different ferrocene (Fc) derivatives (for example decamethylferrocene (DMFc)) [3,4] or tetrathiafulvalene (TTF) [5]. Electrocatalysis of oxygen reduction by different porphyrins [6][7][8][9][10][11] and dodecylaniline [12] has also been studied, and Peljo et al demonstrated a novel fuel cell based on molecular catalysis of oxygen reduction at a liquid/liquid interface [13]. More recently, Olaya et al observed the direct fourelectron reduction of oxygen at the ITIES catalyzed by self-assembled molecular rafts formed of two oppositely charged water-soluble porphyrins [14] and Peljo et al investigated the mechanism of oxygen reduction by so-called cofacial ''Pacman'' type porphyrins at the ITIES [15].…”
Section: Introductionmentioning
confidence: 99%